Association Between Human Immunodeficiency Virus Viremia and Compromised Neutralization of Severe Acute Respiratory Syndrome Coronavirus 2 Beta Variant - Hwa, Shi-Hsia; Snyman, Jumari; Bernstein, Mallory; Ganga, Yashica; Cele, Sandile; Muema, Daniel; Tan, Chee Wah; Khan, Khadija; Karim, Farina; Hanekom, Willem; Bernstein, Leslie; Kaufmann, Stefan H E; et al. (The Journal of infectious diseases, 2023)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may be associated with worse clinical outcomes in people with human immunodeficiency virus (HIV) (PWH). We report anti–SARS-CoV-2 antibody responses in patients hospitalized with coronavirus disease 2019 in Durban, South Africa, during the second SARS-CoV-2 infection wave dominated by the Beta (B.1.351) variant. Methods Thirty-four participants with confirmed SARS-CoV-2 infection were followed up with weekly blood sampling to examine antibody levels and neutralization potency against SARS-CoV-2 variants. Participants included 18 PWH, of whom 11 were HIV viremic. Results SARS-CoV-2–specific antibody concentrations were generally lower in viremic PWH than in virologically suppressed PWH and HIV-negative participants, and neutralization of the Beta variant was 4.9-fold lower in viremic PWH. Most HIV-negative participants and antiretroviral therapy–suppressed PWH also neutralized the Delta (B.1.617.2) variant, whereas the majority of viremic PWH did not. CD4 cell counts <500/μL were associated with lower frequencies of immunoglobulin G and A seroconversion. In addition, there was a high correlation between a surrogate virus neutralization test and live virus neutralization against ancestral SARS-CoV-2 virus in both PWH and HIV-negative individuals, but correlation decreased for the Beta variant neutralization in PWH. Conclusions HIV viremia was associated with reduced Beta variant neutralization. This highlights the importance of HIV suppression in maintaining an effective SARS-CoV-2 neutralization response. People with human immunodeficiency virus viremia elicited lower neutralizing antibody titers against infection with the Beta variant of severe acute respiratory syndrome coronavirus 2 and the majority were unable to cross-neutralize the Delta variant.